Effectiveness and safety of CD22 and CD19 dual‐targeting chimeric antigen receptor T‐cell therapy in patients with relapsed or refractory B‐cell malignancies: A meta‐analysis - Thi Thuy Nguyen; Nguyen Thanh Nhu; Chia‐Ling Chen; Chiou‐Feng Lin (Cancer Medicine, 2023)
Abstract Background The efficacy of CD22 or CD19 chimeric antigen receptor T (CAR‐T) cells in the management of acute lymphoblastic leukemia (ALL) and non‐Hodgkin lymphoma (NHL) was observed. Because antigen loss and lack of CAR‐T‐cell persistence are the leading causes of progressive disease following single‐antigen targeting, we evaluated CD22/CD19 dual‐targeting CAR‐T‐cell therapy efficacy and safety in relapsed/refractory B‐cell malignancies. Methods The Web of Science, PubMed, Cochrane, and Embase databases were searched until July 2022. Patients confirmed with any relapsed/refractory B‐cell hematological malignancies were included regardless of age, gender, or ethnicity, receiving CD22 and CD19‐dual‐targeting CAR‐T‐cell therapy. The studies conducted on patients with coexisting other cancer were excluded. We used random‐effect models to explore the outcome, and heterogeneity was investigated by subgroup analysis. Results Fourteen studies (405 patients) were included. The pooled overall response (OR) and complete remission (CR) were 97% and 93%, respectively, for ALL patients. The 1‐year proportions of overall survival (OS) and progression‐free survival (PFS) were 70% and 49%, respectively. For NHL, OR occurred in 85% of patients, and 57% experienced CR. The results illustrated that the 1‐year OS and 1‐year PFS were 77% and 65%, respectively. The subgroup analysis showed that the dual‐targeting modality achieved higher CR in the following cases: coadministration of CD22/CD19‐CAR‐T cells and third‐generation CAR‐T cells combined with ASCT and BEAM pretreatment. The ALL and NHL groups seemed similar in treatment‐related toxicity: all grade cytokine release syndrome (CRS), severe CRS, and neurotoxicity occurred in 86%, 7%, and 12% of patients, respectively. Conclusions Our meta‐analysis demonstrated that the CD22/CD19 dual‐targeting CAR‐T‐cell strategy has high efficiency with tolerable adverse effects in B‐cell malignancies.